Analysis of the development of capture fish and aquaculture production in Egypt (1996–2005) - Abdelhamid Algayd (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2008)
The paper describes the characteristics of fish growing and fish-production development in Egypt, and focused on the analysis of contribution of aquaculture production by environment in total fish production within the defined reference period 1996 to 2005. Statistical methods were applied to evaluate the state of aquaculture production including mean coefficient of growth and mean coefficient of change. There is also presented short-time point and interval extrapolation prediction of studied events. Methods of regression and correlation analysis and development trends were applied for the mathematical-statistical analysis. The aim of this paper is to present prospective analysis to help both policy maker and technical specialist to improve the development of national aquaculture sector.